2021
DOI: 10.3390/polym13213745
|View full text |Cite
|
Sign up to set email alerts
|

Production and Characterization of Polyethylene Terephthalate Nanoparticles

Abstract: Microplastic (MP) pollution represents one of the biggest environmental problems that is further exacerbated by the continuous degradation in the marine environment of MPs to nanoplastics (NPs). The most diffuse plastics in oceans are commodity polymers, mainly thermoplastics widely used for packaging, such as polyethylene terephthalate (PET). However, the huge interest in the chemical vector role of micro/nanoplastics, their fate and negative effects on the environment and human health is still under discussi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 57 publications
2
17
0
Order By: Relevance
“…Recently, Lionetto et al reported on the production of PET nanoparticles via a stepwise grinding and sieving of PET pellets. [18] Like our observations, their work also suggests that high mechanical energy input typically causes nanoparticles to re-weld if they are not immediately colloidally stabilized. Polystyrene on the other hand is brittle at ambient conditions, which may explain the fact that re-welding processes failed to prevent the formation of PS nanoparticles in the study of Ekvall.…”
Section: Resultssupporting
confidence: 82%
“…Recently, Lionetto et al reported on the production of PET nanoparticles via a stepwise grinding and sieving of PET pellets. [18] Like our observations, their work also suggests that high mechanical energy input typically causes nanoparticles to re-weld if they are not immediately colloidally stabilized. Polystyrene on the other hand is brittle at ambient conditions, which may explain the fact that re-welding processes failed to prevent the formation of PS nanoparticles in the study of Ekvall.…”
Section: Resultssupporting
confidence: 82%
“…PET in micro and nanoscale has been reported as pollutants in the environment [36] and in marine litter [37], nevertheless, there are scarce studies about their toxicity due to the difficult isolation and quantification. Recently, authors such as Magri [23], Rodriguez-Hernandez [24] and Lionetto [38] have developed some reliable strategies for producing polyethylene terephthalate nanoparticles (PET-NPs), an environmentally relevant and representative nanoplastic from plastic pollution. PET-NPs (224 ± 46 d.nm) produced by Rodriguez-Hernandez and colleagues, which maintains the ultrastructure and the chemical composition from their origin and analogous to pristine material [24], has been already used as a model in the identification and characterization of nanoplastics in environment matrices [39].…”
Section: Introductionmentioning
confidence: 99%
“…An incremental trend was observed in the mechanical properties of the FS-welded sample without alteration of the crystal structure, proving the effectiveness of the proposed orbital FSW system. Using the integrated areas below the crystalline peaks A c and the broad amorphous halo A a in the XRD pattern, the degree of crystallinity ( X XRD ) was determined from the following equation [ 27 ]: …”
Section: Resultsmentioning
confidence: 99%